Zoometric characterization of backyard hens from indigenous communities - Vázquez-Mendoza, Paulina; Hernández-Melchor, Gloria Isela; Hernández-Morales , Jahdai; Bottini-Luzardo, María Benedicta; Saavedra Jiménez, Luis Antonio (Ecosistemas y Recursos Agropecuarios, 2025)
Backyard chickens play a significant role in rural communities by contributing to both household economies and cultural practices. However, limited information is available regarding the environment in which they are raised and their phenotypic characteristics. The objective of this study was to characterize the phenotype of chickens raised under backyard production system. The study was conducted in five indigenous communities in the municipality of Ayutla de los Libres, Guerrero, Mexico. A total of 419 reproductively active adult birds (107 males and 312 females) were evaluated. The recorded traits included live weight; breast circumference; lengths of the body, wing, tarsus and thigh; as well as plumage, tarsi, and skin color; and comb type. Quantitative traits were analyzed using completely randomized design, correlation and principal component analysis, and qualitative traits through descriptive statistical methods. The birds were classified as medium-size and exhibited phenotypic variability influenced by sex and locality of origin. Males showed a moderately harmonious body, while females displayed a weakly harmonious profile. Live weight and tarsus length were the most influential traits in determining body size. Most birds had dark plumage (red and black), yellow tarsi, white skin and a simple comb. Further studies are needed to evaluate their productive potential and the genetic basis of their adaptation to warm environments
Keywords: Poultry; conservation; diversity; morphometry; genetic resource